The evaluation of reporting of patient-reported outcomes in MDD: A meta-epidemiological study of clinical trials. (June 2022) - Minley, Kirstien; Smith, Caleb A.; Batioja, Kelsi; Andriana Peña, B.S.; Shepard, Samuel; Heigle, Benjamin; Kee, Micah; Wise, Audrey; Hillman, Cody; Ottwell, Ryan; Hartwell, Micah; Vassar, Matt
Abstract: Major depressive disorder (MDD) is a multifaceted disease that profoundly affects quality of life. Patient reported outcomes (PROs) are used in randomized controlled trials (RCTs) to better understand patient perspectives on interventions. Therefore, we sought to assess the completeness of reporting PROs in RCTs addressing MDD. We identified RCTs evaluating MDD containing a PRO measure published between 2016 and 2020 from MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials. Inclusion of studies was performed in duplicate. The completion of reporting of RCTs was assessed using the Consolidated Standards of Reporting Trials (CONSORT-PRO) adaptation. Bivariate regression analyses were used to evaluate reporting completeness and trial characteristics. A total of 49 RCTs were included in our analysis, with a mean CONSORT-PRO completion score of 56.7% (SD = 17.3).Our findings show a significant association with completeness of reporting and the following: secondary PRO trials were less completely reported as compared to primary PRO trials (t = −3.19, p = .003); studies with a follow-up period between six months and year were more completely reported as compared to three months or less (6 months to a year, t = 2.34, p = .024); and increased trial sample size was associated with more completeness of reporting (t = 3.17, p = .003). As compared to brain stimulation, the intervention types classified as combination, other, and psychotherapy had greater completeness of reporting (combination, t = 2.35, p = .024; other, t = 3.13, p = .003; psychotherapy, t = 3.41, p = .001). There were no other significant findings. Our study found the completeness of PRO reporting to be inconsistent in RCTs regarding MDD. Moreover, we advocate for the need to establish a core outcome set relevant to the management of adults diagnosed with MDD and facilitate training on the application of PRO data.